Effect of fruits of Opuntia elatior Mill on mast cell degranulation - Sanjay P Chauhan; N R Sheth; B N Suhagia (Wolters Kluwer Medknow Publications, 2015)
Background: The presence of potentially active nutrients and their multifunctional properties make prickly pear a perfect candidate for the production of phytopharmaceutical products. Among the numerous Opuntia species, bioactive compounds have been isolated and characterized primarily from Opuntia ficus-indica, Opuntia polycantha, Opuntia stricta, Opuntia dilleni for various medicinal properties. Objective: Based on the traditional use of prickly pear for enhancement of immune function, the objective of the present study to evaluate the effect of prickly pear on mast cell degranulation function. Materials and Methods: The Opuntia fruit juice (OFJ) (10-200 μl/ml) were studied for the effect on sensitized rat peritoneal mast cell degranulation induced by immunological (egg albumin), and nonimmunological (compound 48/80) stimuli and compared with that of the reference standard, sodium cromoglycate and ketotifen (10 μg/ml). Results and Conclusion: The OFJ exhibited significantly (P < 0.001) concentration dependent inhibition of mast cell degranulation. The IC 50 value of OFJ was found 12.24 and 18 μl/ml for immunological and nonimmunological induced mast cell degranulation, respectively. The betacyanin is an active principle compound in prickly pear that may responsible for mast cell stabilizing action.